1991
DOI: 10.1111/j.1539-6924.1991.tb00583.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Fatalities from Waterborne Radon (Rn‐222)

Abstract: A model of the biokinetics of radon in the human body following ingestion is developed from existing data. Calculations of the probability of cancer fatality from use of radon-laden water in the home then are presented. The pathways of emanation and ingestion are examined and shown to lead to roughly equal risks. The probability of fatal cancer resulting from lifetime use of water at a radon concentration of 1 pCi/L is shown to be 1 X 10(-6), with a reasonable range between 2 X 10(-7) and 5 X 10(-6). The allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Because radon is relatively insoluble in water, water use releases radon into the indoor air and contributes to the total indoor-airborne radon concentration. Ingestion of radon in water may also pose a direct health risk through irradiation of sensitive cells in the gastrointestinal tract and other organs once it is absorbed into the bloodstream ( , ). Thus, radon in drinking water could potentially produce adverse health effects in addition to lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Because radon is relatively insoluble in water, water use releases radon into the indoor air and contributes to the total indoor-airborne radon concentration. Ingestion of radon in water may also pose a direct health risk through irradiation of sensitive cells in the gastrointestinal tract and other organs once it is absorbed into the bloodstream ( , ). Thus, radon in drinking water could potentially produce adverse health effects in addition to lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies demonstrating that indoor air radon is associated with a significant risk for lung cancer, 7,[10][11][12][13][14][15] but there has been only one epidemiological study of groundwater radon exposure and lung cancer and this was an ecological study for mortality 17 at the county level that found positive and significant associations. There is general consensus on the biological and physical plausibility of groundwater radon leading to stomach cancer; 8,9,16 however, there has only been one epidemiological study, with a small sample size and lack of control of confounders, 4 to directly measure this association, which showed an insignificant association. Our study is the first epidemiological analysis finding a significant positive association between groundwater radon exposure and lung cancer incidence rates, and the first to find that an increase of 100 Bq/l in groundwater radon concentration increases the odds that both lung cancer cases (OR ¼ 1.12, 95% CI ¼ 1.04, 1.22) and stomach cancer cases (OR ¼ 1.24, 95% CI ¼ 1.03, 1.49) are members of a cancer cluster, after controlling for confounding factors and spatial autocorrelation.…”
Section: Discussionmentioning
confidence: 99%
“…7,[10][11][12][13][14] The International Agency for Research on Cancer concluded there is sufficient evidence that radon and its progeny cause lung cancer in humans 15 . Ingestion of radon is also thought to be associated with lung cancer; however, the literature for the groundwater or drinking-water routes of exposure and lung cancer is limited to biokinetic models 8,16 and one ecological epidemiology analysis of mortality. 17 Although the source of contamination, subsurface geology containing radon or its parent chemicals, is often the same for indoor air and groundwater radon, their effect on lung cancer cannot be assumed to be the same because they have differing environmental levels (since air radon enters the home via infiltration through the soil and home structure, whereas groundwater enters through the private well), different routes of exposure (primarily inhalation for indoor air radon and ingestion for groundwater radon 8 ), and are subject to different remediation measures (air versus water).…”
Section: Introductionmentioning
confidence: 99%
“…The ingestion risk is however under debate because of the variability between differing risk estimates. For example, the risks from ingesting radon from water has been shown to be equal to those from inhalation (Crawford-Brown 1991). The problems with these ingestion risk estimates are the great uncertainties associated with parameters inject@ into the risk calculations, with the uncertainties due to little infomation on the effects of ingesting radon (Federal Register 1991).…”
Section: Radon the Epa And North Carolinamentioning
confidence: 99%